TELEPSYCHIATRY AS A TOOL FOR IMPROVING ACCESS TO MENTAL HEALTH CARE: SOCIAL AND SYSTEM IMPLICATIONS – A NARRATIVE REVIEW - Jeremi Leon Jasiński; Maciej Tomasz Wieczorek; Kamila Teresa Kańska; Anna Krzysztofik; Alicja Maria Mitan; Karolina Krawczyk; Karolina Magda Leszczyńska; Weronika Napierała; Karolina Julia Hak; Aleksandra Maria Tomaszewska (International Journal of Innovative Technologies in Social Science, 2026)
Objective: To examine the extent to which telepsychiatry improves access to mental health care and to analyze its broader social and system implications, with particular attention to equity, service organization, and public policy. Methods: This narrative review synthesizes evidence from 38 peer-reviewed publications published between 2019 and 2025 and included in the predefined bibliography. The literature was analyzed thematically across four domains: access and equity, clinical effectiveness and quality of care, implementation and provider experience, and policy and governance conditions. Key findings: The reviewed literature indicates that telepsychiatry can reduce geographic and logistical barriers, improve continuity of care, and expand service reach, especially in rural and underserved settings. Evidence also suggests that telepsychiatric models may provide clinically meaningful and, in many contexts, comparable care to face-to-face services when supported by appropriate organizational structures. At the same time, the benefits of telepsychiatry are unevenly distributed. Limited broadband access, inadequate devices, low digital literacy, lack of privacy at home, and persistent socioeconomic disadvantage may restrict uptake and reproduce existing inequalities. The literature further shows that long-term effectiveness depends on implementation strategies, workforce readiness, reimbursement models, regulatory flexibility, quality standards, and data protection safeguards. Conclusion: Telepsychiatry should be understood not as a universally sufficient substitute for in-person care, but as a policy-sensitive and system-dependent tool for improving access to mental health services. Its long-term value depends on equitable digital infrastructure, sustainable governance, and carefully designed models of care.